Financial capability and differences in age and ethnicity - Mokhtar, Nuradibah; Sabri, Mohamad Fazli; Ho, Catherine Soke Fun (Korea Distribution Science Association, 2020)
The objective of this study is to disclose the effect of socio-demographic characteristics such as, age and ethnicity which is comprised of Malay, Chinese, Indian and Others on four financial capability domains namely planning ahead, managing money, choosing products and staying informed. A closed ended self-administered questionnaire was disseminated to a total of 2000 respondents among four types of groups which consist of FELDA or rural area residents, private sector employees, government sector employees and youth in institutions of higher learning in Malaysia. Those four groups were selected to cover a wide range of Malaysian population. 500 respondents were involved in this study for each types of groups through purposive sampling technique. Analysis of Variance (ANOVA) and analysis via Statistical Package for Social Science (SPSS) was utilized in this study. The results revealed that age has significant effect on planning ahead, managing money, choosing products and staying informed. Whereas, ethnicities were found to have no effect on financial capability except planning ahead domain. It is suggested that more devotion should be placed on research and professional training in building respondents' financial capability. Furthermore, government and non-government organizations should develop a comprehensive approach to intensify their financial capability and upgrade their standards of living especially of financially vulnerable households.